2008
DOI: 10.1002/ange.200705591
|View full text |Cite
|
Sign up to set email alerts
|

Supramolekulare Blockcopolymere mit Cucurbit[8]uril in Wasser

Abstract: Sei mein Gast! Ein supramolekulares amphiphiles Diblockcopolymer wurde mithilfe einer molekularen „Handschelle“ aus Cucurbit[8]uril hergestellt (siehe Bild). Es geht einen hierarchischen Selbstorganisationsprozess ein, der zur Bildung einer tertiären kompartimentierten Nanostruktur führt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
30
1

Year Published

2009
2009
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(31 citation statements)
references
References 48 publications
(46 reference statements)
0
30
1
Order By: Relevance
“…[34][35][36][37][38][39][40][41] Scherman et al and we have reported the use of such interactions to construct supramolecular polymers. [42,43] The essential feature of this interaction is that the distance between donor and acceptor molecules is significantly reduced when they are both encapsulated in the cavity of a host, which can enhance charge-transfer interactions. This idea can also be extended to other host-enhanced noncovalent interactions.…”
Section: Introductionmentioning
confidence: 99%
“…[34][35][36][37][38][39][40][41] Scherman et al and we have reported the use of such interactions to construct supramolecular polymers. [42,43] The essential feature of this interaction is that the distance between donor and acceptor molecules is significantly reduced when they are both encapsulated in the cavity of a host, which can enhance charge-transfer interactions. This idea can also be extended to other host-enhanced noncovalent interactions.…”
Section: Introductionmentioning
confidence: 99%
“…[5,6] Although covalent attachment of two components to form peptide amphiphiles has been extremely successful, [7,8] the synthetic versatility and the ability to respond to external triggers remains limited. [16,17] One of the larger macrocycles in this family, CB [8], can be used as a "molecular handcuff" to join two molecules together in a non-covalent fashion, [18,19] and has been applied to form biomaterials such as polymer-protein conjugation and protein dimerization. [9][10][11][12][13][14][15] Cucurbit[n]urils (CB[n]) are a family of macrocyclic hosts known to form inclusion complexes with selectivity and high binding affinity in aqueous media.…”
mentioning
confidence: 99%
“…[10] A less travelled route employs hostguest interactions as the driving force for polymerization. [8,11,12,13] The main reason for its limited use is that very high association constants (! 10 5 ) are required to obtain polymers with high molecular weight.…”
Section: Introductionmentioning
confidence: 99%